European trade policy at the service of geopolitics? Requirements for new instruments from the perspective of family businesses - Gabriel Felbermayr (Stiftung Familienunternehmen, 2022)
Last year, a total of 1,700 new protectionist measures were introduced around the world. This marks a new record. Even before the war in the Ukraine, political disputes were increasingly handled using economic sanctions - an approach which leads to high economic costs. Family companies in particular are dependent on the international division of labour.
Keywords: 330